Comparative research of the most popular third-party and built-in iOS applications for time-management - Zhelturguzova, Lyazzat (2019)
The bachelor thesis topic is focused on the comparison and analysis of iOS applications for improving user's productivity and time-management. The main goal is to investigate ways the communication between the user and the application, user interaction, and compatibility with Apple and third-party services based on important criteria, described in the user and market research.This bachelor thesis contains the theoretical part, where will be described the main definitions related to time-management, iOS system and features, user interface and user experience.Finally, it describes a solution that will achieve the balance between the Application's efficiency and user comfort based on detailed research and comparison